2017
DOI: 10.1371/journal.pone.0173675
|View full text |Cite
|
Sign up to set email alerts
|

Role of muscle IL-6 in gender-specific metabolism in mice

Abstract: The aim of the present work was to further explore the physiological roles of muscle-derived IL-6. Adult-floxed and conditional skeletal muscle IL-6 knock out male and female mice were used to study energy expenditure (indirect calorimetry at rest and during treadmill exercise, and body temperature cycle during the light phase) and energy intake (response to fast/refeeding). We also evaluated the responses to leptin and the activity of the insulin signalling pathway in skeletal muscle and liver by phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 51 publications
3
19
0
Order By: Relevance
“…The antiandrogen Flutamide decreases the treadmill endurance of rats, but does not change O 2max and running economy 26 . Here, the exercise-induced submaximal O 2 and CO 2 up to O 2max were similar between sexes, as previously described 11 , 12 , 27 . Only one study demonstrated increased female submaximal O 2 during treadmill test, which further reinforces the hypothesis of females’ worst running economy 27 .…”
Section: Discussionsupporting
confidence: 82%
“…The antiandrogen Flutamide decreases the treadmill endurance of rats, but does not change O 2max and running economy 26 . Here, the exercise-induced submaximal O 2 and CO 2 up to O 2max were similar between sexes, as previously described 11 , 12 , 27 . Only one study demonstrated increased female submaximal O 2 during treadmill test, which further reinforces the hypothesis of females’ worst running economy 27 .…”
Section: Discussionsupporting
confidence: 82%
“…Most cytokines and chemokines involved with innate and stress-induced immunity are directly or indirectly inhibited by glucocorticoid receptor activation (27). IL-6 needs particular consideration because it has important metabolic effects that support lipolysis in adipose tissue and glucose homeostasis during exercise, some of these effects are general effects (21) and some sex specific (44). Exogenous IL-6 administration improves thermal tolerance and tissue protection from heat stroke (46).…”
Section: Andmentioning
confidence: 99%
“…Indeed, tissue-specific knockout mice confirm that IL6 plays an important role in the obesity response (15)(16)(17)(18)(19)(20)(21)(22)(23).…”
mentioning
confidence: 97%